Incentives for Optimal Management of Age-structured Fish Populations - Martin Quaas; Till Requate; Kirsten Ruckes; Anders Skonhoft; Niels Vestergaard (Verein für Socialpolitik, 2010)
We study optimal fishery management in an age-structured, bio-economic model where two age classes can be harvested independently. We show that the optimal amount of catch differs with age classes, and we derive conditions under which it is optimal to harvest only one age class. Our main policy implication is that optimal age-structured harvesting can be implemented by a single total allowable catch (TAC) and tradable harvesting quotas, where the latter are specified in terms of the number of fish harvested rather than in terms of biomass. In this case, gear restrictions (such as mesh-size prescriptions) turn out to be obsolete. We then apply our model to Eastern Baltic cod fishery.
Keywords: Q22; Q57; Q28; 330; fishery management; optimal harvesting; harvesting fees; bioeconomics; age-structured model